Extra-abdominal Intestinal Anastomosis: A New Technique and Problem-solving Tool in Many Critical Circumstances - Faruquzzaman (Mediscope, 2023)
Background: Anastomosis leakage following intestinal anastomosis and the development of septic complications is a major problem for surgeons in certain clinical situations. There are many circumstances, where surgeons are in great trouble for decision making, where exteriorization of the intestine or performing a primary anastomosis is a risky procedure with a very fatal outcome. The purpose of this paper is to introduce a newer technique “extra-abdominal intestinal anastomosis”. Objective: The ultimate aim of this research is to assess the outcome of this new procedure compatible with such situations with different important surgical aspects. Methods: This prospective study was conducted with a total of 42 patients of extra-abdominal small intestinal done in Khulna Medical College Hospital (KMCH), Bangladesh. The study period was from January 2017 to November 2020. All the operations were done on emergency setup. Convenient purposive sampling was the sampling technique. Results: In this research, approximately 28.6% (12 patients) were undergone emergency operations for gangrenous intestine, followed by 19.0% (08 patients) for postoperative abdominal sepsis. Another important indication was strangulated hernia (07 patients, 11.9%). Extra-abdominal intestinal anastomosis on a trial basis was done in 42 patients in KMCH. Excellent results were observed. Overall mortality and morbidity have been reduced. Moreover, due to fewer complications, hospital stays, and costs have been reduced, on the contrary, patient compliance has been increased. The mortality rate with extra-abdominal intestinal anastomosis was 14.3%, whereas it was reported to be very high previously in KMCH in many circumstances. Extra-intestinal leakage was observed in approximately 26.2% of cases. Approximately in 14.3% patients of with extra-abdominal leakage, extra-abdominal repair was possible without major consequences. Early internalization of the intestinal anastomosis with the closure of the abdominal wall was possible on the 7th to 14th postoperative day in approximately 61.9% of patients with good results. Conclusion: The newer method, extra-abdominal intestinal anastomosis is a resilient procedure in many emergencies with fewer complications, less hospital staying, reduced mortality, morbidity rate and excellent patient compliance. Mediscope 2023;10(2): 56-62